DGI-049 Octeotride in Gastrointestinal Angiodysplasia. (12th March 2013) - Nazco, GJ; González, I; Gutierrez, F; Valcárcel, C; Rodríguez, I; Pérez, M; Pecos, P; Virgós, T; Bullejos, M; Chafer, M
Abstract : Background: Gastrointestinal angiodysplasia (GIAD) may either be asymptomatic or induce overt or occult bleeding with a high risk of recurrence. Numerous therapeutic options are available but an evidence bass is lacking. Purpose: To analyse costs and improve the clinical parameters in patients with GIAD after intramuscular administration of long-acting octreotide (Oc-LAR) 10 mg/month. Materials and Methods: Retrospective observational study from January to December 2011. We reviewed the medical records of patients who were prescribed long-acting Octreotide for GIAD. Clinical data (haemoglobin, vials of iron needed, blood transfusions) and demographic characteristics of the patients were tabulated using Excel. We compared clinical results pre- and post-Oc-LAR use. The x 2 test was used for category variables, and the t-test was used for continuous variables with normal distribution using SPSS statistical software. Clinical and monetary value were derived from publicly available data. The study perspective was from the hospital management point of view. Results: 17 patients were included in the study, 11 were men and 6 women. The mean age was 75.2 years. The direct costs were €350 per red blood cell transfusion, €167 per iron administration and €694.95 for Oc-LAR. The mean Hb levels were 9.0 g/dl and 9.6 g/dl (p < 0.0001) before and after treatment. Blood transfusions decreased from 1.8 to 1.7 (P = 0.258). However iron requirements were higher after treatment started:. 2.5 vials of iron, up from 1.9 (P = 0.027). And there was an increase in hospital admissions annually 3.3 vs. 2.3 before treatment (P = 0.311). So Oc-LAR use increased the average annual cost per patient by 8, 401.6€ without stopping disease progression. Conclusions: Pharmacological treatments are typically considered in refractory cases of endoscopic failure and recurrent bleeding. Oc-LAR seems to be more suitable in terms of efficacy and tolerance according to the bibliography. However, our study shows that Octreotide long-acting formulation treatment was not cost effective and failed to stop the natural evolution of the disease. No conflict of interest.